Volume 6: Turbomachinery, Parts A, B, and C 2008
DOI: 10.1115/gt2008-51109
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Active Methods of Flow Control on Compressor Blade Cascade Flow

Abstract: This paper deals with active methods of flow control, especially synthetic jet flow control. A synthetic jet was used for flow control in the compressor blade cascade to reduce the vortex structure and reduce the value of the loss coefficients. The output slot of the synthetic jet actuator was situated on the side wall on the connecting line of the leading edges of the blades. The direction of the synthetic jet was perpendicular to the main flow. The synthetic jet excitation is more effective and more efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…Gmelin et al 14 employed both steady and unsteady actuation to control secondary flows in a highly loaded compressor cascade. Results indicated that compared with other flow control techniques which were able to delay flow separation and improve the cascade performance, the synthetic jet actuation appeared to be more efficient, which is consistent with the findings of Zheng et al, 18 Matejka et al, 19 and Traficante et al and De Giorgi et al 20,21 In addition, the control mechanisms of synthetic jets on reducing losses were revealed by De Giorgi et al 21 Using large eddy simulation, they found that the increased values of root-mean-square (RMS) velocity near the actuation slot were related to the enhancement of momentum mixing, which transported kinetic energy from the jet flow to the boundary layer, helping the low energy fluid to overcome severe streamwise adverse pressure gradient. Another experimental study was performed on a low-speed highly loaded compressor cascade for the control of boundary layer separation and secondary flows by Zander et al 22 Amplitude variations proved the jet velocity ratio of 1.0 to be the most efficient one with the maximum loss reduction.…”
Section: Introductionsupporting
confidence: 87%
“…Gmelin et al 14 employed both steady and unsteady actuation to control secondary flows in a highly loaded compressor cascade. Results indicated that compared with other flow control techniques which were able to delay flow separation and improve the cascade performance, the synthetic jet actuation appeared to be more efficient, which is consistent with the findings of Zheng et al, 18 Matejka et al, 19 and Traficante et al and De Giorgi et al 20,21 In addition, the control mechanisms of synthetic jets on reducing losses were revealed by De Giorgi et al 21 Using large eddy simulation, they found that the increased values of root-mean-square (RMS) velocity near the actuation slot were related to the enhancement of momentum mixing, which transported kinetic energy from the jet flow to the boundary layer, helping the low energy fluid to overcome severe streamwise adverse pressure gradient. Another experimental study was performed on a low-speed highly loaded compressor cascade for the control of boundary layer separation and secondary flows by Zander et al 22 Amplitude variations proved the jet velocity ratio of 1.0 to be the most efficient one with the maximum loss reduction.…”
Section: Introductionsupporting
confidence: 87%
“…As reported by other authors like Matejka et al [8] and Zheng et al [9], flow control with synthetic jet actuators is highly efficient. Both authors report that the amount of saved work reducing the total pressure loss exceeds the sum of energy spend.…”
Section: Active Flow Control Efficiencymentioning
confidence: 75%
“…In the past, some of these AFC methods have been investigated in axial compressors with the focus on rotor instabilities and boundary layer separation on the rotor blades [5]. Passive and active flow control applications, with the focus on boundary layer separation and secondary flow structures were tested in several ways, mostly on linear stator cascades [6,7]. Experimental and numerical investigations of steady state methods for controlling strong secondary flow structures, as well as boundary layer separation were presented by Nerger [8].…”
Section: Introductionmentioning
confidence: 99%